2019
DOI: 10.1002/app.48461
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of performance and fouling resistance of polyamide reverse osmosis membranes using acrylamide and TiO2 nanoparticles under UV irradiation for water desalination

Abstract: The purpose of this research is to explain the surface modification of fabricated polyamide reverse osmosis (RO) membranes using UV-initiated graft polymerization at different irradiation times (15, 30, 60, and 90 s) and various acrylamide concentrations (10, 20, and 30 g L −1 ). Also, coating of membranes surface with various concentrations of TiO 2 nanoparticles (10, 20, 30, and 50 ppm) followed by the same UV irradiation times was investigated. After that, the membranes modification was done by grafting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…It has been reported that UV irradiation was used to graft hydrophilic and foulingresistant poly 2-[(methacryloyloxy)ethyl] dimethyl-(3-sulfopropyl) ammonium hydroxide (PSPE) [102] and PEG [103] to the surface of PA TFC. To improve the anti-fouling capabilities of the PA TFC RO membrane, Asadollahi et al used UV-initiated grafting of acrylamide mixed with TiO 2 nanoparticles [102].…”
Section: Irradiation-induced Graft Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that UV irradiation was used to graft hydrophilic and foulingresistant poly 2-[(methacryloyloxy)ethyl] dimethyl-(3-sulfopropyl) ammonium hydroxide (PSPE) [102] and PEG [103] to the surface of PA TFC. To improve the anti-fouling capabilities of the PA TFC RO membrane, Asadollahi et al used UV-initiated grafting of acrylamide mixed with TiO 2 nanoparticles [102].…”
Section: Irradiation-induced Graft Polymerizationmentioning
confidence: 99%
“…It has been reported that UV irradiation was used to graft hydrophilic and foulingresistant poly 2-[(methacryloyloxy)ethyl] dimethyl-(3-sulfopropyl) ammonium hydroxide (PSPE) [102] and PEG [103] to the surface of PA TFC. To improve the anti-fouling capabilities of the PA TFC RO membrane, Asadollahi et al used UV-initiated grafting of acrylamide mixed with TiO 2 nanoparticles [102]. Due to the overwhelming cross-linking action over chain scission, selective layer densification was seen after a short irradiation duration of <90 s. Due to the inclusion of hydrophilic TiO 2 , the membrane's salt rejection ability enhanced without affecting the water flow.…”
Section: Irradiation-induced Graft Polymerizationmentioning
confidence: 99%
“…There are only a few works devoted to the application of composite polyamide/TiO 2 in membrane technology, particularly for the preparation of membranes for nanofiltration [ 27 , 28 , 29 , 30 , 31 , 32 ], reverse osmosis [ 33 , 34 , 35 , 36 , 37 , 38 ], pervaporation [ 39 ], and microfiltration [ 40 ]. In [ 27 , 28 , 29 , 30 ], the nanofiltration thin film nanocomposite (TFN) membranes based on PA were subjected to the modification with TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For reverse osmosis (RO), the modification with TiO 2 of PA membrane was carried out by various approaches: the introduction of fillers into polymer matrix [ 33 ] or the coating of fillers on the surface [ 34 , 35 , 36 , 37 , 38 ]. In [ 33 ], a RO PA membrane was developed by the incorporation of GO and TiO 2 to enhance the salt rejection and filtration performance for purification of drinking water and treatment of wastewater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation